2017
DOI: 10.4103/jfmpc.jfmpc_250_17
|View full text |Cite
|
Sign up to set email alerts
|

Thrombocytopenia in HIV patients coinfected with tuberculosis

Abstract: Thrombocytopenia is one of the most common hematological manifestations seen in HIV patients with approximately 40% of the patients developing thrombocytopenia during their course of illness. Opportunistic infection like tuberculosis is a rare but curative cause of thrombocytopenia in these patients. Clinically, it is a challenge to determine the exact cause and decide the treatment of thrombocytopenia in these patients as both infections can lead to significant thrombocytopenia by varied mechanisms. The treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Thrombocytopenia was observed in 1.6% of the cases in the current study. The most common reasons being thrombocytopenia was, peripheral destruction of platelets due to cross-reactivity of HIV antibodies, apoptosis of megakaryocytes due to direct HIV infection and abnormal and dysfunctional platelet production [ 54 ]. The prevalence was similar with a finding reported by Oshikoya et al [ 55 ] found to be 1.4%.…”
Section: Discussionmentioning
confidence: 99%
“…Thrombocytopenia was observed in 1.6% of the cases in the current study. The most common reasons being thrombocytopenia was, peripheral destruction of platelets due to cross-reactivity of HIV antibodies, apoptosis of megakaryocytes due to direct HIV infection and abnormal and dysfunctional platelet production [ 54 ]. The prevalence was similar with a finding reported by Oshikoya et al [ 55 ] found to be 1.4%.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of thrombocytopenia among PTB patients was 8% while it was 20% among PTB-HIV coinfected patients. Different mechanisms such as immune mechanisms, bone marrow fibrosis, direct megakaryocyte infection, and hypersplenism had been implicated as possible causal factors for thrombocytopenia in PTB-HIV coinfected patients [3640].…”
Section: Discussionmentioning
confidence: 99%
“…In primary thrombocytopenia, the causes differ in different stages of HIV, where autoimmune destruction predominates in early stages, while defective thrombopoiesis predominates in the late stages [1]. In secondary thrombocytopenia, opportunistic infections are important causes and TB is the most common [2,4,5].…”
Section: Discussionmentioning
confidence: 99%